Effect of Respiratory Growth on the Metabolite Production and Stress Robustness of Lactobacillus casei N87 Cultivated in Cheese Whey Permeate Medium - Ricciardi, Annamaria; Zotta, Teresa; Ianniello, Rocco Gerardo; Boscaino, Floriana; Matera, Attilio; Parente, Eugenio (Frontiers in Microbiology, 2019)
Cheese whey permeate (WP) is a low-cost feedstock used for the production of biomass and metabolites from several lactic acid bacteria (LAB) strains. In this study, Lactobacillus casei N87 was cultivated in an optimized WP medium (WPM) to evaluate the effect of anaerobic and respiratory conditions on the growth performances (kinetics, biomass yield), consumption of sugars (lactose, galactose, glucose) and citrate, metabolite production (organic acids, volatile organic compounds) and stress survival (oxidative, heat, freezing, freeze-drying). The transcription of genes involved in the main pathways for pyruvate conversion was quantified through Real Time-PCR to elucidate the metabolic shifts due to respiratory state. Cultivation in WPM induced a diauxic growth in both anaerobic and respiratory conditions, and L. casei N87 effectively consumed the lactose and galactose present in WPM. Genomic information suggested that membrane PTS system and tagatose-6-P pathway mediated the metabolism of lactose and galactose in L. casei N87. Respiration did not affect specific growth rate and biomass production, but significantly altered the pyruvate conversion pathways, reducing lactate accumulation and promoting the formation of acetate, acetoin and diacetyl to ensure the redox balance. Ethanol was not produced under either cultivation. Pyruvate oxidase (pox), acetate kinase (ack), α-acetolactate decarboxylase (ald), acetolactate synthase (als) and oxaloacetate decarboxylase (oad) genes were up-regulated under respiration, while L-lactate dehydrogenase (ldh), pyruvate formate lyase (pfl), pyruvate carboxylase (pyc) and phosphate acetyltransferase (pta) were down regulated by oxygen. Transcription analysis was consistent with metabolite production, confirming that POX-ACK and ALS-ALD were the alternative pathways activated under aerobic cultivation. Respiratory growth affected the production of volatile compounds useful for the development of aroma profile in several fermented foods, and promoted the survival of L. casei N87 to oxidative stresses and long-term storage. This study confirmed that the respiration-based technology coupled with cultivation on low-cost medium may be effectively exploited to produce competitive and functional starter and/or adjunct cultures. Our results, additionally, provided further information on the activation and regulation of metabolic pathways in homofermentative LAB grown under respiratory promoting conditions.